SOI Single-Electron Transistors (SET) design and process development - Amiza, Rasmi; Mohammad Nuzaihan, Md Nor; Uda, Hashim (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.